Structural mechanism of insulin receptor activation by a dimeric aptamer agonist - Junhong Kim; Hyeonjin Na; Si-Young Choi; Eun Ju Oh; Hyunsook Lee; Sung Ho Ryu; Na-Oh Yunn; Yunje Cho (Experimental and Molecular Medicine)
Abstract Insulin binding to the insulin receptor (IR) triggers signaling pathways that regulate glucose uptake and cell growth. In previous work, we identified a DNA aptamer, A62, which partially activates the IR. During engineering aptamers for improved in vivo stability, we discovered that crosslinking two A62 aptamers with linkers of varying lengths led to full phosphorylation of the IR, although activation remained selective to the AKT pathway. Here, to elucidate the mechanism behind this aptamer-induced full activation of the IR, we determined the structure of the IR in complex with a dimeric form of A62 (A62D) linked by an eight-nucleotide connector. We identified three distinct conformations of the IR: arrowhead-shaped, pseudo-arrowhead-shaped and pseudo-gamma-shaped. The pseudo-gamma-shaped conformation closely resembles the structure of a fully active IR bound by a single insulin molecule. In these configurations, only one A62 monomer (A62M) within the A62D dimer binds to the IR dimer. This binding brings the IR monomers into close proximity, promoting intermolecular trans-phosphorylation. Our findings provide valuable structural insights for the development of novel therapeutic strategies targeting the IR.